A novel nematic tri-carbazole as a hole-transport material for solution-processed OLEDs. Issue 1 (2nd January 2021) - Hu, Guang; Kitney, Stuart P.; Billa, Muralidhar Reddy; Kelly, Stephen M.; Lambert, Brian; Harrison, William
ABSTRACT: Two structural isomers of alkyl-substituted tri-carbazoles were synthesised to study the effect of the substitution pattern on their liquid crystalline behaviour and conductivity and performance in test OLEDs. The isomer with a 2, 7-disubstitution pattern in the central carbazole exhibits a monotropic nematic phase, a high conductivity up to 10 Cd A −1 and is suitable as a hole-transport material for solution-processed OLEDs, achieving a high efficiency. The tri-carbazole isomer with a 3, 6-substitution pattern, in the central carbazole, does not exhibit observable liquid crystalline behaviour, exhibits conductivity values two orders of magnitude lower than that of its 2, 7-disubstituted isomer and performs poorly in OLEDs with the same configuration. GRAPHICAL ABSTRACT: Two structural isomers of alkyl-substituted tri-carbazoles A and B exhibit significantly different liquid crystalline behaviour, conductivity and performance in test OLEDs dependent upon their molecular shape. uf0001